Peran Orang Tua Dalam Membangun Fondasi Keagamaan Anak-Anak: Perspektif Teologi Pendidikan Agama Kristen - Harun Puling; Noverlina Zendrato; Sandra R Tapilaha (Jurnal Budi Pekerti Agama Kristen dan Katolik, 2024)
This study discusses the crucial role of parents in building the religious foundation of children, focusing on the perspective of Christian religious education theology. Parents are viewed as primary agents in shaping the faith and spiritual values ​​of children. Through a theological approach, this study explores how parents can fulfill their role as religious educators within the household. Concepts such as communal prayer, scripture reading, and other religious practices are important in building the religious foundation of children. Additionally, the study outlines the importance of parents understanding Christian theology as the basis for the religious education of their children. By considering the principles of Christian religious education theology, parents can guide their children towards healthy spiritual growth and strengthen their relationship with God. Practical implications of this study include the implementation of contextual and relevant religious education methods tailored to the needs of children, as well as parents' efforts to consistently serve as models of faith for them. Thus, a profound understanding of the role of parents in building the religious foundation of children from the perspective of Christian religious education theology can provide valuable guidance for religious education practices at the household level.